THE USE OF DIGITAL STORY TELLING TO IMPROVE STUDENTS LISTENING ABILITY AT SMP N 1 TONDANO - Emia Sura Bina Purba; Nihta V. F. Liando; Merlin M. Maukar (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2023)
The goal of this study was to employ Digital Storytelling to help ninth-grade students at SMP Negeri 1 Tondano enhance their listening skills. Pre-experimental research with a quantitative approach and a one group pretest posttest design were used to collect data for this study from the students' hearing exams. This study's sample included 21 pupils from SMP Negeri 1 Tondano. The post-test outperformed the pre-test. The mean post-test value is = 8 9.05, and the standard deviation is = 93.5. The mean value of the pre test is 71.7, and the standard deviation is 75.25. Because the post-test findings outperform the pre-test results, it can be inferred that employing digital storytelling is helpful for developing the listening skills of ninth grade students at SMP Negeri 1 Tondano. Suggestions include teachers paying greater attention to how to educate students properly, so that students are readily engaged in learning and listening to English through the use of media or technologies.